The myofibroblast, biological activities and roles in eye repair and fibrosis. A focus on healing mechanisms in avascular cornea - Rocher, Maxime; Robert, Pierre-Yves; Desmoulière, Alexis (Eye (London), 2020)
Tissue healing is one of the mysteries of modern medicine. Healing involves complex processes and many cellular types, amongst which the myofibroblast plays a major role. In the eye, when needed, myofibroblasts can be found from the cornea to the retina, derived from a wide variety of different cells, and aimed at effectively repairing tissue damage. Myofibroblast differentiation requires transforming growth factor (TGF)-β1, the presence of specific extracellular matrix components such as the ED-A domain of fibronectin, and mechanical tension. Control of this process may, in some cases, be abnormal leading to development of fibrotic tissue, which alters and compromises the integrity of the original tissue. The eye is no exception to this rule with normal visual function, a highly demanding process, only possible in a fully integrated organ. The cornea, a transparent protective tissue and first dioptre of the eye, has the particularity of being entirely avascular and very richly innervated under normal physiological conditions. However, these anatomical features do not prevent it from developing myofibroblasts in the event of a deep corneal lesion. Activated by growth factors such as TGF-β1 and platelet-derived growth factor from the aqueous humour, tears or corneal epithelial cells, myofibroblasts can cause corneal scarring, sometimes with devastating consequences. Understanding the factors involved in healing and its signalling pathways, will potentially enable us to control corneal healing in the future, and thus avoid fibrotic ocular surface disease and the blindness that this may induce. Currently, this issue is the subject of very active research and development with the aim of discovering new antifibrotic therapies.